Pengaruh Penambahan Program Blood Flow Restriction Training Pada Pasien Post Operasi Anterior Cruciate Ligament Reconstruction Fase 1: Case Report - Dendi Brian Saputra; Surya Saputra Perdana; Abdurrasyid Abdurrasyid (Jurnal Kesehatan dan Fisioterapi, 2022)
Patients after postoperative Anterior Cruciate Ligament Reconstruction, generally experience several problems such as pain, swelling, decreased knee ROM, decreased muscle strength, decreased leg muscle mass, and decreased quality of daily life. Some of the above problems can be overcome more quickly using the new method with BFRT in the standard phase 1 post ACLR program. The patient, a 32-year-old man, has suffered from an ACL injury since 1 year ago, due to a twisted knee when he fell from a motorcycle and just had ACLR surgery on his left knee 7 days ago with a hamstring tendon autograft. After 7 days postoperatively, the patient came to the ARA Physio clinic with complaints of left knee pain, swelling, difficulty bending the knee, and difficulty walking. The physiotherapy program is scheduled twice a week for 4 weeks and evaluated every 2 weeks to find out its progress. The physiotherapy program includes exercises to reduce pain and swelling in the left knee, increase ROM in the left knee, increase left leg muscle mass by adding BFRT to standard phase 1 ACL exercises. Measurement of pain using VAS, swelling and atrophy using a meterline, ROM using a goniometer, and knee functional using the WOMAC Index. In evaluating the progress of the patient after being given an intervention for 4 weeks, the results showed a decrease in left knee swelling, an increase in left knee ROM, a decrease in left knee pain scale, an increase in left leg muscle mass, and an increase in knee functional ability.Keywords: Physiotherapy Interventions, Post Operation Anterior Cruciate Ligament Reconstruction, Blood Flow Restriction Training.